Communication Skills between the Relatives and the Doctors of Patients with Cancer Treated in Radiation Oncology: A Cross-sectional Questionnaire Study - ALSAN ÇETİN, İLKNUR; AKAY, SITKI UTKU (KARE PUBL, 2021)
OBJECTIVE To evaluate the communication between relatives and the doctors of patients with cancer treated in the radiation oncology department using a questionnaire composed of two sections. METHODS Relatives of 168 patients were selected through simple randomization after having obtained informed consent from the patients. A questionnaire form, which was developed based on the patient-physician communication scale, which had the sub-dimensions of information, empathy and confidence and included questions regarding socio-demographic data, and which used a Likert-type scale, was applied. Statistical analyses were performed using the Mann-Whitney U test and the Kruskal Wallis test. RESULTS A statistically significant difference was determined in the information and empathy sub-dimensions concerning the gender and the education level of the relatives (p=0.03, p=0.01, p=0.001) and the frequency of seeing the doctor and the doctor's tolerance (p=0.007, p=0.02); in the confidence possession sub-dimension, a difference was found between the age groups of the relatives and the tumor groups of the patients (p=0.039, p=0.002), duration of seeing the doctor and talking with the doctor (p=0.004, p=0.009), between the relatives' praying and all sub-dimensions (p=0.009, p<0.0001); in the information sub-dimension, a difference was found with regard to the duration of therapy (p=0.03). It was also determined that all relatives wished to obtain correct information and have confidence in the doctor. CONCLUSION The results show the expectations and the content of information, empathy and confidence sub-dimensions of the communication process between relatives and the doctors of the patients.
Keywords: Communication skills; relatives of patients with cancer; HEALTH INFORMATION; OUTCOMES; CARE; PHYSICIANS; INTERNET; PREFERENCES; DIAGNOSIS; EMPATHY; PARENT; VIEWS